2018
DOI: 10.1371/journal.pone.0193087
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an effective, low cost, Free/open access 3D-printed stethoscope

Abstract: The modern acoustic stethoscope is a useful clinical tool used to detect subtle, pathological changes in cardiac, pulmonary and vascular sounds. Currently, brand-name stethoscopes are expensive despite limited innovations in design or fabrication in recent decades. Consequently, the high cost of high quality, brand name models serves as a barrier to clinicians practicing in various settings, especially in low- and middle-income countries. In this publication, we describe the design and validation of a low-cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 24 publications
1
34
0
Order By: Relevance
“…However, before designing a device to be compatible with chemical cleaning, it is important to realize that stiffness and printed resolution are critical to assess the feasibility of 3Dprinted medical tools. This has been (partially) done for some designs including umbilical cord clamps, surgical retractors, and stethoscopes, but not for surgical instruments such as forceps [6][7][8]. Since these issues are device-specific, the usability of each of these 3D-printed tools must be proven in a clinical setting.…”
Section: Implications For Designing Three-dimensional Printedmentioning
confidence: 99%
See 1 more Smart Citation
“…However, before designing a device to be compatible with chemical cleaning, it is important to realize that stiffness and printed resolution are critical to assess the feasibility of 3Dprinted medical tools. This has been (partially) done for some designs including umbilical cord clamps, surgical retractors, and stethoscopes, but not for surgical instruments such as forceps [6][7][8]. Since these issues are device-specific, the usability of each of these 3D-printed tools must be proven in a clinical setting.…”
Section: Implications For Designing Three-dimensional Printedmentioning
confidence: 99%
“…It has been suggested that three-dimensional (3D)-printed medical tools could reduce the equipment shortage and solve repair problems [6][7][8][9][10]. A large variety of designs have been proposed, including knobs for controlling microscopes, a low-cost videolaryngoscope, a stethoscope, umbilical cord clamps, and surgical instruments [6,8,9,[11][12][13]. For example, Bhatia et al proposed a high-utility surgical toolkit that includes various types of commonly used forceps, clamps, and a retractor, based on devices previously described in the literature [6].…”
Section: Introductionmentioning
confidence: 99%
“…Rene Laennec first introduced the stethoscope in 1819 [1] and ever since, physicians have examined the respiratory and circulatory systems with the stethoscope. A multitude of respiratory conditions and disorders can be diagnosed by hearing crackles, wheezing, or plural rubs.…”
Section: Introductionmentioning
confidence: 99%
“…The wide use of stethoscopes has made them readily available for purchase at higher than necessary costs. 1 Contact author: popkinrachel@knights.ucf.edu Several medical companies and brands manufacture and sell stethoscopes, some even relying on online resellers like Amazon for distribution. MDF Instruments, for instance, sells stethoscopes ranging between $24.99 and $165.70.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation